Papaverine Enhances the Oncolytic Effects of Newcastle Disease Virus on Breast Cancer In Vitro and In Vivo - Sura Akram; Ahmed Majeed Al-Shammari; Hayder B. Sahib; Majid Sakhi Jabir (International Journal of Microbiology)
Breast cancer is a lethal disease in females worldwide and needs effective treatment. Targeting cancer cells with selective and safe treatment seems like the best choice, as most chemotherapeutic drugs act unselectively. Papaverine showed promising antitumor activity with a high safety profile and increased blood flow through vasodilation. At the same time, it was widely noticed that virotherapy using the Newcastle disease virus proved to be safe and selective against a broad range of cancer cells. Furthermore, combination therapy is favorable, as it attacks cancer cells with multiple mechanisms and enhances virus entrance into the tumor mass, overcoming cancer cells’ resistance to therapy. Therefore, we aimed at assessing the novel combination of the AMHA1 strain of Newcastle disease virus (NDV) and nonnarcotic opium alkaloid (papaverine) against breast cancer models in vitro and in vivo. Methods. In vitro experiments used two human breast cancer cell lines and one normal cell line and were treated with NDV, papaverine, and a combination. The study included a cell viability MTT assay, morphological analysis, and apoptosis detection. Animal experiments used the AN3 mouse mammary adenocarcinoma tumor model. Evaluation of the antitumor activity included growth inhibition measurement; the immunohistochemistry assay measured caspase protein expression. Finally, a semiquantitative microarray assay was used to screen changes in apoptotic proteins. In vitro, results showed that the combination therapy induces synergistic cytotoxicity and apoptosis against cancer cells with a negligible cytotoxic effect on normal cells. In vivo, combination treatment induced a significant antitumor effect with an obvious regression in tumor size and a remarkable and significant expression of caspase-3, caspase-8, and caspase-9 compared to monotherapies. Microarray analysis shows higher apoptosis protein levels in the combination therapy group. In conclusion, this study demonstrated the role of papaverine in enhancing the antitumor activity of NDV, suggesting a promising strategy for breast cancer therapy through nonchemotherapeutic drugs.